2021
DOI: 10.3389/fphys.2020.614590
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation: A Possible Explanation for Long-Lasting Exercise Intolerance in Mild COVID-19 Survivors?

Abstract: Since the outbreak of the coronavirus (COVID-19) pandemic, most attention has focused on containing transmission and addressing the surge of critically ill patients in acute care settings. As we enter the second phase of the pandemic, emphasis must evolve to post-acute care of COVID-19 survivors. Persisting cardiorespiratory symptoms have been reported at several months after the onset of the infection. Information is lacking on the pathophysiology of exercise intolerance after COVID-19. Previous outbreaks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 49 publications
5
84
1
7
Order By: Relevance
“…It thus appears that circulatory impairment might be the missing link that could explain some of the residual symptoms in post-COVID-19 syndrome, but we should keep in mind that the mechanism remains obscure. The ventilatory inefficiency observed in our symptomatic cohort is also observed in the hyperventilation syndrome [36], which has been recently suggested as a potential mechanism of the post-COVID-19 syndrome [37]. In fact, this syndrome has been described in broad lung conditions, such as acute pulmonary embolism, pneumonia, chronic interstitial lung diseases, and after viral infections [36].…”
Section: Rationale For Post-covid-19 Symptom Persistencesupporting
confidence: 70%
See 3 more Smart Citations
“…It thus appears that circulatory impairment might be the missing link that could explain some of the residual symptoms in post-COVID-19 syndrome, but we should keep in mind that the mechanism remains obscure. The ventilatory inefficiency observed in our symptomatic cohort is also observed in the hyperventilation syndrome [36], which has been recently suggested as a potential mechanism of the post-COVID-19 syndrome [37]. In fact, this syndrome has been described in broad lung conditions, such as acute pulmonary embolism, pneumonia, chronic interstitial lung diseases, and after viral infections [36].…”
Section: Rationale For Post-covid-19 Symptom Persistencesupporting
confidence: 70%
“…Finally, another potential mechanism could be the autonomic dysfunction. Maladaptive function of the autonomic nervous system in COVID-19 survivors may contribute to the persistence of fatigue, shortness of breath, and palpitations [37]. Consistent with this hypothesis, Dorelli et al observed a slower heart rate recovery suggestive of dysautonomia among post-COVID-19 patients with ventilatory inefficiency [39].…”
Section: Rationale For Post-covid-19 Symptom Persistencementioning
confidence: 92%
See 2 more Smart Citations
“…Further studies with a larger, more representative cohort (including patients with critical respiratory involvement) and over a longer period are needed for better understanding of the respiratory longterm impairment after SARS-CoV-2 infection in children and adolescents. The discrepancy between subjective persistent respiratory complaints and normal pulmonary function might be caused by functional respiratory disorders, for example hyperventilation, as already described in adults [26,27].…”
Section: Discussionmentioning
confidence: 67%